Preisentscheidungen in sequenziell gekoppelten Privathandels- und Double-Auction-Märkten ; Eine experimentelle Untersuchung - Lemke, Fabian (KIT Scientific Publishing, 2014)
Experimentel investigation of individual influencing factors on decisions in price negotiations is the central research goal of this thesis. A private negotiation and a double auction market are sequentially linked. The influence of storability of the traded good is examined in a model that includes price and trade quantity as causally linked variables. It can be shown, that preference for the market form among buyers and sellers is dependent on the storabitlity of the traded good.